(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Allergic diseases (AD) take the third place after cardiovascular and oncological diseases (and in some ecologically unfavorable regions they come out on top). It has also been noted that over the past 30 years, during each decade, the incidence of allergies worldwide has doubled [6, 7]. This article provides an overview and information about the etiological factors of allergic diseases.